Web crippling performance of pultruded GFRP C sections strengthened by fibre-reinforced epoxy composite - Lakhiar M.T.; Kong S.Y.; Bai Y.; Miah M.J.; Syamsir A. (Elsevier Ltd, 2024)
This study aims to improve the web crippling performance of pultruded glass fibre-reinforced polymer (GFRP) C sections using fibre-reinforced epoxy composite (FEC). The strengthened GFRP C sections were subjected to two loading conditions: interior-two-flange (ITF) and exterior two-flange (ETF). The parameters considered were bearing lengths, FEC strengthening length and thicknesses. Two failure modes, namely web-flange junction failure and web buckling failure were observed for the pultruded GFRP C sections under ETF loading conditions as the bearing length changed. While the combination of the web-flange junction and FEC crushing failures were observed under ITF loading conditions at 20 mm and 50 mm bearing lengths. Furthermore, the average web crippling capacity of strengthened GFRP C sections improved by up to 426 % and 488 %, in comparison to control samples under ETF and ITF loading conditions, respectively. The average web crippling capacity of pultruded GFRP C sections increased up to 45 % when the bearing length increased from 20 mm to 50 mm. The finite element (FE) outcomes showed an agreement with experimental results in the context of failure patterns, load-displacement profiles and web crippling capacities. Finally, equations were proposed to estimate the web crippling capacity of pultruded GFRP C sections strengthened with FEC. 2023 Elsevier Ltd